Governança migratória e invisibilidade da população idosa: os desafios para o acolhimento e a integração de migrantes e refugiados idosos no Brasil - Nabarrete, Pietra Cortez (2023)
Population aging and the growth of forced migration flows are related processes which demand appropriate responses from the public authorities and society. In general, however, they are phenomena that are rarely studied together in the academic literature. This article focuses on the analysis and identification of the main constraints on the effective reception and integration of the elderly migrant and refugee population in Brazil, based upon a multilevel governance of migration which includes Operation Welcome. The purpose of this paper is to contribute to studies that analyze the forced displacement of the elderly population, in light of the management of Venezuelan migration in Brazil. To this end, this research consulted the literature and documents on the subject and conducted interviews with employees of agencies and entities involved in the reception of elderly migrants and refugees. Among the challenges encountered were the lack of an age-based focus in the formation of governance structures for migration, the tendency to securitize the migration agenda, and the scarcity of disaggregated data, all of which hamper the formulation and implementation of policies that address the multiple vulnerabilities of the elderly migrant and refugee population